Pengaruh Desain Kemasan, Variasi Produk Dan Kualitas Produk Terhadap Minat Beli Konsumen Produk Bolu Tape Pada Toko Oleh-Oleh Anisa Di Rogojampi - Anggraini, Distiara; Sudirman, Rio; Hurotul A, Winda (LITERATUS, 2024)
In running a business that is never free from competition, especially in terms of marketing, entrepreneurs compete to find ways to get their consumers by improving their company's performance to receive maximum profits, business people must know how to implement the right strategy to attract consumers, including creating attractive packaging designs, large product variations, and good product quality to increase consumer buying interest. The aim of this research is to determine the influence of packaging design, product variety and product quality on consumer buying interest at the Anisa Gift Shop in Rogojampi. This research uses a questionnaire method and data processing uses multiple linear regression analysis, coefficient of determination, partial test (t test), and simultaneous test (f test). The distribution of questionnaires was distributed to 70 respondents who were consumers at the Anisa Gift Shop. The results of this research show that the variables packaging design (X1), product variety (X2) and product quality (X3) partially (t test) or simultaneously (f test) have a positive and significant influence on consumer buying interest, with a coefficient of determination (Adjust R Square) obtained is 0.652 or 65.2%, meaning that 65.2% of Purchase Interest can be explained by Independent variables including Packaging Design (X1), Product Variation (X2), and Product Quality (X3), while the remaining 34.8% is likely to be explained by other independents who were not included in this study.